POTENSI ABU CANGKANG KERANG DARAH (Anadara Granosa) SEBAGAI ADSORBEN ION TIMAH PUTIH - G. Afranita; S. Anita; T. A. Hanifah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The waste of blood clam seashells (Anadara granosa) can be used as adsorbent of tin.Blood clam seashells was calcinated at 800 0 C of ±9 hours. Blood clam seashellscontained CaO . The aim of this study was to see potential of blood clam seashell ash asabsorbent of tin. The research was conducted by contacting was tin ion and blood clamseashell ash with the variation of concentration. Tin analysis performed by using atomicabsorption spectroscopy (AAS). The results showed that optimal absorption occurs at30 mg/L, at 15 hours was 66,53%.